Identification and characterization of auxin response factor (ARF) family members involved in fig (Ficus carica L.) fruit development - Wang, Haomiao; Huang, Hantang; Shang, Yongkai; Song, Miaoyu; Ma, Huiqin (PeerJ, 2022)
The auxin response factor (ARF) combines with AuxREs cis-acting elements in response to auxin to regulate plant development. To date, no comprehensive analysis of ARF genes expressed during fruit development has been conducted for common fig (Ficus carica L.). In this study, members of the FcARF gene family were screened, identified in the fig genome database and their features characterized using bioinformatics. Twenty FcARF genes were clustered into three classes, with almost similar highly conserved DBD (B3-like DNA binding domain), AUX/IAA (auxin/indole-3-acetic acid gene family) and MR domain structure among class members. Analysis of amino acid species in MR domain revealed 10 potential transcription activators and 10 transcription inhibitors, and 17 FcARF members were predicted to be located in the nucleus. DNA sequence analysis showed that the ARF gene family consisted of 4–25 exons, and the promoter region contained 16 cis-acting elements involved in stress response, hormone response and flavonoid biosynthesis. ARF genes were expressed in most tissues of fig, especially flower and peel. Transcriptomics analysis results showed that FcARF2, FcARF11 and FcARF12, belonging to class-Ia, were stably and highly expressed in the early development stage of flower and peel of ‘Purple peel’ fig. However, their expression levels decreased after maturity. Expression of class-Ic member FcARF3 conformed to the regularity of fig fruit development. These four potential transcription inhibitors may regulate fruit growth and development of ‘Purple Peel’ fig. This study provides comprehensive information on the fig ARF gene family, including gene structure, chromosome position, phylogenetic relationship and expression pattern. Our work provides a foundation for further research on auxin-mediated fig fruit development.
Keywords: Ficus carica L.; Auxin response factor; Gene family; Expression analysis; Fruit development